Effective Facial Expression Recognition System Using Artificial Intelligence Technique - Yousif, Imad S.; Rashid, Tarik A.; Shamsaldin, Ahmed S.; Abdulhameed, Sabat A.; Abdullah, Abdulhady Abas (Kurdistan Journal of Applied Research, 2024)
Facial expressions are the most basic non-verbal method people use to communicate feelings, intentions and reactions without words. Recognizing these facial expressions accurately is essential for a variety of applications — such as tools that use our faces to interact with computers (human-computer interaction, or HCI), security systems and emotionally intelligent artificial intelligence technologies. As the complexities surrounding these relationships have become better understood, it has allowed us to develop increasingly more complex systems for identifying and detecting facial expressions of different emotions. This paper presents an improved performance of the Facial Expression Recognition (FER) systems via augmentation in Artificial Neural Networks and Genetic Algorithms, two renowned artificial intelligence techniques possessing disparate strengths. ANNS are inspired by the neural architecture of human brain capable of learning and recognizing patterns in unchartered data after trained examples, on the other hand GAs come from fundamental principles underlying natural selection perform optimization process based-on evolutionary methods which includes fitness evaluation, comparison, selection, crossover, and mutation. The research is an effort to mitigate the problems pertaining with conventional methods, like overfitting and generalization fault in order design FER model which has potential for performing much more accurately. A hybrid ANN-GA model that uses Petri Nets and production systems is proposed for the real-time video sequence analysis with high precision in predicting different dynamic facial activities of anger, surprise, disgust, joy, sadness and fear from emotion faces. Importantly, results on the study show that this integrated model has a large-scale promoting effect in emotion detection upon varied scenes and is therefore generalizable to many domains from security and surveillance over biomedicine up to interactive AI-driven systems. Implications for implementing real-time and context-aware recognition of human emotions based on AI technologies are far-reaching as they demonstrate the potential that hybrid AI systems offer at enhancing emotion deciphering.